2007
DOI: 10.1007/s00167-006-0254-z
|View full text |Cite
|
Sign up to set email alerts
|

Double-bundle versus single-bundle anterior cruciate ligament reconstruction: a prospective, randomize clinical study

Abstract: Anatomical observation and biomechanical studies have shown that the anterior cruciate ligament (ACL) mainly consists of two distinct bundles, the anteromedial (AM) bundle and posterolateral (PL) bundle. Conventional single-bundle ACL reconstruction techniques have focused on the restoration of the AM bundle while giving limited attention to the PL bundle. The purpose of this prospective, randomized clinical study is to compare the outcomes of ACL reconstruction when using either double-bundle or single-bundle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
264
4
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 293 publications
(290 citation statements)
references
References 27 publications
15
264
4
7
Order By: Relevance
“…[2][3][4] Several prospective clinical trials have reported significantly better outcomes in anatomic DB procedures than the SB procedures in terms of pivot shift test and anterior laxity. [5][6][7][8] Several workers have…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] Several prospective clinical trials have reported significantly better outcomes in anatomic DB procedures than the SB procedures in terms of pivot shift test and anterior laxity. [5][6][7][8] Several workers have…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15][16] On the other hand, only a clinical report 17 has introduced a remnant-preserving technique for double-bundle ACL reconstruction, in which 2 femoral tunnels and one tibial tunnel were made, although anatomic double bundle ACL reconstruction procedures have recently attracted notice because of biomechanical advantages in laboratory studies. [18][19][20][21][22][23][24][25][26][27][28] However, no previous studies have shown clinical evidence about utility of the ACL remnant tissue preservation in ACL reconstruction as of yet. To verify whether preservation of the ACL remnant tissue can really improve proprioceptive functions and enhance revascularization, we should conduct a randomized comparative trial with a sufficient number of patients to compare the 2 ACL reconstruction procedures with and without the remnant preservation in terms of proprioception and revascularization of the graft.…”
Section: Introductionmentioning
confidence: 99%
“…Given the biomechanical advantages of performing double bundle ACL reconstruction over non-anatomic single bundle reconstruction it is not surprising that there have been numerous clinical studies comparing double and single bundle ACL reconstruction [38,[41][42][43][44][45][46][47]. Several of these reveal improved anterior and rotational stability with DB reconstruction [38,43,45,47] however many show no significant difference [42,44,46].…”
Section: Clinical Outcomesmentioning
confidence: 99%
“…Jarvela reported on outcomes at 2 years reporting improved knee kinematics post operatively for DB compared with SB reconstruction [41] however Siebold compared both SB and DB reconstructions and found no advantage in using the a DB technique [45] In 2008 Meredick et al performed a meta-analysis and found no difference between SB and DB ACL reconstruction [42]. Since this meta-analysis a few studies have compared lateralized or anatomic single bundle reconstructions with double bundle.…”
Section: Clinical Outcomesmentioning
confidence: 99%